1999
DOI: 10.1029/1998pa900028
|View full text |Cite
|
Sign up to set email alerts
|

Similar glacial and Holocene deep water circulation inferred from southeast Pacific benthic foraminiferal carbon isotope composition

Abstract: Abstract. We present Holocene and last glacial maximum (LGM) oxygen and carbon isotope measurements on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(69 citation statements)
references
References 83 publications
9
60
0
Order By: Relevance
“…The δ 13 C records from these sites are similar to one another (Fig. 1b) and to shorter records from the North Pacific (Keigwin, 1998), the southeast Pacific (Matsumoto and Lynch-Stieglitz, 1999), and other western equatorial Pacific sites (Herguera et al, 1992;Mix et al, 1991). The PDW and SCW δ 13 C stacks (Fig.…”
Section: Regional δ 1c Stackssupporting
confidence: 48%
See 1 more Smart Citation
“…The δ 13 C records from these sites are similar to one another (Fig. 1b) and to shorter records from the North Pacific (Keigwin, 1998), the southeast Pacific (Matsumoto and Lynch-Stieglitz, 1999), and other western equatorial Pacific sites (Herguera et al, 1992;Mix et al, 1991). The PDW and SCW δ 13 C stacks (Fig.…”
Section: Regional δ 1c Stackssupporting
confidence: 48%
“…The δ 13 C of NCW is fairly well constrained by data from six sites above 2300 m in the North Atlantic. However, there is some evidence for δ 13 C gradients between different NCW components (Matsumoto and Lynch-Stieglitz, 1999;Millo et al, 2006), particularly before 600 kyr ago (Raymo et al, 2004). In the Pacific and South Atlantic, the availablility of δ 13 C data is limited by poor carbonate preservation in these regions.…”
Section: Data Limitationsmentioning
confidence: 99%
“…Ganopolski and Rahmstorf (2001) found that deep-water formation south of Iceland was a stable climate mode, with overturning north of the GIS Ridge being a marginally unstable state. This is consistent with the tendency for adjustment between Labrador Sea and Greenland Sea convection modulated by the NAO (Dickson et al, 1996) and the evidence for the usual state of the glacial THC to be of a similar strength to today (Yu et al, 1996;Matsumoto and Lynch-Stieglitz, 1999), but based south of the GIS Ridge (Weinelt et al, 1996). Thus, switches in the formation region of NADW are related to modulation of local surface density, with possible feedbacks into the North Atlantic atmospheric circulation.…”
Section: Thermohaline Catastrophessupporting
confidence: 70%
“…This suggests that the glacial-interglacial d 13 C amplitude changes recorded by E. exigua cannot be related to changes in the C org flux to the seafloor, which occur much earlier, but most likely change with glacial-interglacial variations in the nutrient inventory of bottom water masses. Indeed, the glacial-interglacial d 13 C amplitudes recorded by E. exigua in cores MD02-2589 and MD02-2588 during glacial Terminations I and II of 0.34% and 0.41% compare well with the estimated mean ocean d 13 C change of 0.32% [Matsumoto and Lynch-Stieglitz, 1999]. Taken at face value, consistency of d 13 C amplitudes along the E. exigua isotope record with mean ocean d 13 C change would suggest that during glacial periods (MIS 2 and MIS 6) there was a persistent contribution of a well-ventilated water mass at intermediate depths at the Agulhas Plateau with a d 13 C signature similar to present-day NADW.…”
Section: Stable Carbon Isotopessupporting
confidence: 62%
“…Taken at face value, consistency of d 13 C amplitudes along the E. exigua isotope record with mean ocean d 13 C change would suggest that during glacial periods (MIS 2 and MIS 6) there was a persistent contribution of a well-ventilated water mass at intermediate depths at the Agulhas Plateau with a d 13 C signature similar to present-day NADW. A possible continued northern component water influence is in line with inferences from 213 Pa/ 230 Th [Yu et al, 1996], paired benthic-planktonic d 18 O [Matsumoto and Lynch-Stieglitz, 1999;Matsumoto et al, 2001] and detrital Nd isotopic records [Bayon et al, 2003] that all suggest only minor changes in water mass structure and circulation in the area on glacialinterglacial timescales. As well as the suggestion of only little change in the nutrient inventory for deep waters in the Southern Ocean derived from nearly constant glacial and interglacial foraminiferal Cd/Ca values in the region [Boyle, 1992;Oppo and Rosenthal, 1994;Boyle and Rosenthal, 1996].…”
Section: Stable Carbon Isotopesmentioning
confidence: 56%